A two‐phase model for sheet flow regime based on dense granular flow rheology. Issue 2 (4th February 2013) - Revil‐Baudard, T.; Chauchat, J.
Abstract : [1] A two‐phase model having a μ ( I ) rheology for the intergranular stresses and a mixing length approach for the turbulent stresses is proposed to describe the sheet flow regime of sediment transport. In the model, two layers are considered: a dilute suspension layer and a dense sediment bed layer. The concentration profile is obtained from the dilatancy law ϕ ( I ) in the sediment bed layer and from a Rouse profile in the suspension layer. The comparison of velocity profile, concentration profile, and macroscopic parameters (sediment transport rate, thickness, and roughness) with experimental data shows a good agreement. These comparisons demonstrate that the dense granular rheology is relevant to describe intense bed‐load transport in turbulent regime (sheet flow). The transition from the dense static bed to the dilute suspension is well described by the present model. Also, the different regimes of the dense granular rheology seems to be able to capture the transition between collision‐dominant and turbulent‐fluctuations‐dominant sheet flows, depending on the particle's characteristics. Key Points: The dense granular flow rheology is relevant for sheet‐flow modeling Proposition of a layer decomposition based on stresses repartition Transition between collisional/fluid turbulent dominant sheet flow captured